Grid cells on steeply sloping terrain: evidence for planar rather than volumetric encoding - Hayman, Robin M. A.; Casali, Giulio; Wilson, Jonathan J.; Jeffery, Kate J. (Frontiers in Psychology, 2015)
Neural encoding of navigable space involves a network of structures centred on the hippocampus, whose neurons –place cells – encode current location. Input to the place cells includes afferents from the entorhinal cortex, which contains grid cells. These are neurons expressing spatially localised activity patches, or firing fields, that are evenly spaced across the floor in a hexagonal close-packed array called a grid. It is thought that grid cell grids function to enable the calculation of distances. The question arises as to whether this odometry process operates in three dimensions, and so we queried whether grids permeate three-dimensional space – that is, form a lattice – or whether they simply follow the environment surface. If grids form a three-dimensional lattice then a tilted floor should transect several layers of this lattice, resulting in interruption of the hexagonal pattern. We model this prediction with simulated grid lattices and show that on a 40-degree slope the firing of a grid cell should cover proportionally less of the surface, with smaller field size and fewer fields and reduced hexagonal symmetry. However, recording of grid cells as animals foraged on a 40-degree-tilted surface found that firing of grid cells was almost indistinguishable, in pattern or rate, from that on the horizontal surface, with if anything increased coverage and field number, and preserved field size. It thus appears unlikely that the sloping surface transected a lattice. However, grid cells on the slope displayed slightly degraded firing patterns, with reduced coherence and slightly reduced symmetry. These findings collectively suggest that the grid cell component of the metric representation of space is not fixed in absolute three-dimensional space but is influenced both by the surface the animal is on and by the relationship of this surface to the horizontal, supporting the hypothesis that the neural map of space is “multi-planar” rather than fully volumetric.